Longitudinal Quantitative MRI Evaluation of Muscle Involvement in Amyotrophic Lateral Sclerosis - Paoletti, Matteo; Diamanti, Luca; Muzic, Shaun I.; Ballante, Elena; Solazzo, Francesca; Foppoli, Lia; Deligianni, Xeni; Santini, Francesco; Figini, Silvia; Bergsland, Niels; Pichiecchio, Anna (Frontiers in Neurology, 2021)
Biomarkers of disease progression and outcome measures are still lacking for ALS patients. Muscle MRI can be a promising candidate to track longitudinal changes and to predict response to the therapy in clinical trials. Our aim is to apply quantitative muscle MRI in the evaluation of disease progression, focusing on thigh and leg muscles of ALS patients, and to explore the correlation between radiological and clinical scores. We enrolled newly-diagnosed ALS patients, longitudinally scored using the ALS Functional Rating Scale Revised, who underwent a 3T muscle MRI protocol including a 6-point Dixon gradient-echo sequence and multi-echo TSE T2-weighted sequence for quantification of fat fraction (FF), cross-sectional area (CSA), and water T2 (wT2). A total of 12 muscles of the thigh and 6 muscles of the leg were assessed by manual drawing of 18 regions of interest (ROIs), for each side. A group of 11 age-matched healthy controls (HCs) was enrolled for comparison. Results: Fifteen patients (M/F 8/7; mean age 62.2 years old, range 29 - 79) diagnosed with possible (n=2), probable (n=12) or definite (n=1) ALS were enrolled. Eleven patients presented spinal onset, while four of them had initial bulbar involvement. All patients performed MRI at T0, nine of them at T1, and seven of them at T2. At baseline water T2 was significantly elevated in ALS subjects compared to HCs for several muscles of the thigh and mainly for leg muscles. By contrast, FF was elevated in few muscles, and mainly at the level of the thigh. The applied mixed effects model showed that FF increased significantly in the leg muscles over time (mainly in the triceps surae), and that water T2 decreased significantly in line with worsening in the leg subscore of ALSFRS-R, mainly at the leg level and in the anterior and medial compartment of the thigh. Quantitative MRI represents a non-invasive tool that is able to outline the trajectory of pathogenic modifications of muscle in ALS. In particular, wT2 was found to be increased early in the clinical history of ALS and decreased over time, also showing a positive correlation with leg subscore of ALSFR-R.